Strategi Bertindak Tutur Komisif Pada Wacana Iklan Kosmetik - Antika, Helin Dian; , Prof. Dr. Harun Joko Prayitno, M.Hum (2016)
Studies this aims to describe the form of speech acts commissive in cosmetics advertising discourse and describing strategies act said commissive in cosmetics advertising discourse. This research is descriptive qualitative research. This study uses content analysis research design. Researchers studied the language used to offer a product in cosmetics advertising discourse. Basic techniques in this study is a decisive element sorting technique or techniques PUP. Pilah power in question is aggregated power pragmatists. Sorting through the power can be known of speech acts contained in cosmetics advertising discourse. Based on the survey results revealed that the speech act commissive in cosmetics advertising discourse which there are 100 in the strategy aspect commissive speech that is intended, promise, swear and bernadar. Context affecting speech acts commissive in cosmetics advertising is their attempt speakers give confidence to opponents said that using the products offered. The strategy used in speech acts commissive in cosmetics ads above is declarative indirectly. It said declarative indirectly because the ad was actually intends to request the ad reader to use the products offered. However, the advertiser trying to soften or mengimplisitkan these requests into declarative form. Keywords: speech acts commissive, advertising, cosmetics. Abstrak